Implementasi Balanced Scorecard Dalam Pengukuran Kinerja Dinas Lingkungan Hidup Kota Bandung - Dwi Marselina, Resya; Andriyana, Hendra; Taufiq Rachmansyah, Rivan; Salsabiil, Salma; Shofa Shabrina, Syahla (Shofanah Media Berkah, 2025)
This study discusses the implementation of the Balanced Scorecard (BSC) as a strategic performance evaluation tool at the Bandung City Environmental Agency (DLHK). Using a qualitative case study approach, data were collected through interviews and internal document analysis. The results of the study indicate that DLHK has implemented various programs such as “Kang Pisman” and air quality monitoring, but still faces obstacles such as limited human resources, low digitalization, and suboptimal community participation. The implementation of the BSC through four perspectives—finance, customers, internal processes, and learning and growth—has proven to be able to identify gaps and provide strategic direction for more measurable and sustainable performance improvement.